A LETTER FROM SPECIAL EDITION EDITOR IN CHIEF - DR. KHRIEREIZHÜNUO DZÜVICHÜ - Dzüvichü, Khriereizhünuo (International Journal of Research -GRANTHAALAYAH, 2024)
Oriental College Kohima has successfully organised a One-Day Multi-Disciplinary Conference on "Emerging Paradigms in Social Sciences, Humanities & Commerce for the 21st Century" on the 7th of December 2024. Research scholars and teaching faculty from affiliated colleges of Nagaland University participated in the conference, and a total of 13 papers were selected to be published in the International Journal of Research -GRANTHAALAYAH as a special issue titled Emerging Paradigms in Social Sciences, Humanities & Commerce for the 21st Century The distinguished keynote speakers of the conference were Professor Nigamananda Das, Head, Department of English, Nagaland University and Dr. Jasojit Debnath, Associate Professor, Department of Commerce, Nagaland University. The papers were presented with active participation and interaction with topics ranging from Naga history, craftsmanship, self-reliance, and the sheer ingenuity and resilience of the Naga forefathers to topics intensely in tune with nature and surroundings and how the Naga forefathers understood the phenomena of nature and the sky to the benefit of their awareness and survival. The importance of the traditional institutions like the Morung, and social concepts like dignity of labour, work culture and ethics of the Naga forefathers were presented. The presentations shifted gear to recent trends like the changing and challenging roles and dynamic transformation in the status of women and participation of women in Naga politics; the success stories of the farmers of King Chilli in making a community economically stable and self –reliant; inclusivity in education; NEP 2020; status of higher Education in Nagaland, etc. Comparative literature studies found platform with works like ‘Spirited Away’ by Hayao Miyazaki, Japanese animator, filmmaker and manga artist and Easterine Kire’s ‘A Terrible Matriarchy’ being analysed in depth alongside with insightful and thought provoking take on psychoanalytic literary criticism and Naga folklore. Papers dealing with the essence and the allure of folk poetry and the plethora of feelings and emotions of poetry added much discourse on the metrical composition of Tenyimia lyrical poetry in an innovative manner. The conference is organized with the objective to bring together academicians, scientists, researchers, scholars and students to exchange and share their knowledge, experiences and research results on the aspects of advancements in the field of Social Sciences, Humanities and Commerce, based on a multidisciplinary approach through intradisciplinary, interdisciplinary and transdiciplinary research, which would benefit the academic world. The discussions during the paper presentations proved to be a great opportunity for exchanging knowledge among great minds. I express my sincere thanks to the publisher of Granthaalayah Publications for collaborating with Oriental College Kohima to motivate researchers with due recognition. Oriental College Kohima looks forward to take this partnership to the next level with substantial research contributions to promote collaborative studies in the emerging paradigms of Social Sciences, Humanities & Commerce. Sincerely, Dr. Khriereizhünuo Dzüvichü